2007
DOI: 10.1042/bj20061901
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the substrate and inhibitor specificities of human coagulation Factor VIIa

Abstract: The remarkably high specificity of the coagulation proteases towards macromolecular substrates is provided by numerous interactions involving the catalytic groove and remote exosites. For FVIIa [activated FVII (Factor VII)], the principal initiator of coagulation via the extrinsic pathway, several exosites have been identified, whereas only little is known about the specificity dictated by the active-site architecture. In the present study, we have profiled the primary P4-P1 substrate specificity of FVIIa usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…1C). Exceptions were T99A and K192A variants with 30 -50% reduced activity as previously reported (16,29,37). Similarly, FVIIa-catalyzed FIX activation was markedly unaffected by modifications in the FVIIa protease domain (Fig.…”
Section: Screening For Fviia Variants With Alteredsupporting
confidence: 58%
See 1 more Smart Citation
“…1C). Exceptions were T99A and K192A variants with 30 -50% reduced activity as previously reported (16,29,37). Similarly, FVIIa-catalyzed FIX activation was markedly unaffected by modifications in the FVIIa protease domain (Fig.…”
Section: Screening For Fviia Variants With Alteredsupporting
confidence: 58%
“…We focused on the P2-S2 interaction known from FVIIa T99A and T99Y variants to modulate the efficacy of PAR2 cleavage while still preserving PAR2-tethered ligand interactions following activation. The P2 preference of TF⅐FVIIa has previously been determined using combinatorial fluorogenic tetrapeptide substrate libraries (29). To allow for direct comparison we determined the P2 preference of FXa under identical conditions (Fig.…”
Section: This Is Illustrated Inmentioning
confidence: 99%
“…The interaction between the enzyme and the serpin requires a well defined active site, and especially interactions in the substrate binding pockets S1-S4 seem to be crucial (30). We found that FVIIa alone is relatively slowly inhibited by AT with a second-order rate constant of 310 M Ϫ1 s…”
Section: Effect Of Antibodies On Inhibition Of Fviia By At-at Belongsmentioning
confidence: 74%
“…Such 'exosite' interactions are important in enhancing the catalysis of inherently poor enzymes, including metalloproteases 28 and coagulation proteases. 29,30 Since DRONC has no intrinsic preference for Glu over Asp, why is the primary autolytic cleavage site at position 352 conserved as Glu in both D. melanogaster and Drosophila pseudoobscura? To answer this will require some sophisticated experiments, but it could simply be to prevent other caspases, such as DCP-1 and DRICE with the canonical Asp specificity, 16 from adventitiously cleaving DRONC.…”
Section: Discussionmentioning
confidence: 99%